Darkwinged Fungus Gnats, Bradysia spp. (Insecta: Diptera: Sciaridae) - Frank W. Mead; Thomas R. Fasulo (EDIS)
Most species of darkwinged fungus gnats (Sciaridae) feed on fungi and decaying organic matter and are not considered economic problems. A few species, however, attack healthy tissue of such economic plants as potatoes, wheat, red clover, alfalfa, cultivated mushrooms, pine seedlings, and various ornamentals, including tulip bulbs, ferns, begonias, coleus, geraniums, cacti, young orchids, areca palm, and dracaenas. Sciarids are a problem in Florida greenhouses, mostly concerning injury to plants, but also large numbers of flying gnats being an occasional nuisance to workers. This document is EENY-215 (originally published as DPI Entomology Circular No. 186), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2001.